(3GdedNU GdhLjR ddEOGQI hGdJMdjd GdeGdj (B/s - (3GdSYGjOI, ajUd Lejds; (3aQjO, fVGd YHO Gddgs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj ddfTQ hGdJhRjY(B, s, 2004)
(3GdEOGQI GdeGdjI(B- (3GdSjGSGJ GdeGdjI(B- (3eUGOQ GdJehjd(B- (3GdYhGed GdeMOOI dCfhGY GdJehjd(B- (3EOGQI GdehLhOGJ(B- (3GdJMdjd GdeGdj(B- (3COhGJ GdJMdjd GdeGdj(B- (3GdJMdjd GdeGdj HGdfSH(B- (3JMdjd GdJYGOd(B- (3JMdjd GdQaY(B- (3GdJNWjW GdeGdj(B- (3GdQjGVI GdeGdjI(B.s
(3GdeQGLY U(B. 219s
Keywords: (3GdEOGQIs; (3GdEOGQI GdeGdjIs; (3GdJMdjd GdeGdjs